Strategies for Coping with Suicidal Ideation as Expressed by Polytechnic Students in Oyo State - Fadipe, Rasaq Abimbola; Saadu, Yusuf Olatunji; Atoyebi, Mary Omolola Olajumoke; Atoyebi, Oyeniran Kayode (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
This study examined strategies for coping with suicidal ideation as expressed by polytechnic students in Oyo State, Nigeria. The study employed the descriptive survey design. A sample of 450 students was randomly selected and administered questionnaires across various faculties. However, only 443 responses were properly retrieved and analysed for this study. A research instrument, titled: "Strategies for Coping with Suicidal Ideation Questionnaire (SCSIQ)", was used to collect data from the respondents. The content validity of the instrument was done by five experts from the Department of Counselling and Human Development Studies at the University of Ibadan and the reliability was established using test re-test reliability method, which yielded a correlation coefficient of 0.79. The data collected were analysed using both descriptive and inferential statistics at 0.05 level of significance. The findings revealed that polytechnic students cope with suicidal ideation by seeking support from friends when feel overwhelmed, seeking professional counselling services when in distress, and engaging in physical activities (e.g., sports, exercise) to improve their mood. Findings also indicated that there were no significant differences in the strategies for coping with suicidal ideation as expressed by polytechnic students in Oyo State based on age and religion. However, there were significant differences in the strategies for coping with suicidal ideation as expressed by polytechnic students in Oyo State based on gender and place of residence. It was therefore, recommended that students struggling with suicidal ideation should seek help from friends for support, access professional counselling services, engage in physical exercises and relaxation techniques, and set achievable goals to mitigate academic frustration and cope more effectively. Guidance counsellors, social workers, academic advisors, and mental health professionals should provide support services, including mental health counselling, academic advising, social skills training, and guidance, without hesitation to students struggling with suicidal ideation in school.